Role of IDGFs and adenosine signaling in cell survival and energy homeostasis - Brož, Václav (Jihočeská univerzita, 2017)
Two groups of growth regulators were described in Drosophila imaginal disc cell culture Cl.8+. Imaginal disc growth factors (IDGFs) belonging to chitinase-like protein family of carbohydrate binding proteins and Adenosine deaminase-related growth factors (ADGFs), which are active adenosine deaminases influencing homeostasis of key cellular metabolite adenosine. The functions of two of the IDGFs, as well as the effects of extracellular adenosine and its receptor were studied primarily in in vitro cell culture. Our results supported their roles in the regulation of cell survival and energy homeostasis especially in imaginal disc cells. Both the IDGFs and adenosine also play important roles in organismal responses to stress and infection and may interact in vivo.
Role of IDGFs and adenosine signaling in cell survival and energy homeostasis
Keywords: Drosophila; chitinase like proteins; cell culture; adenosine; imaginal disc cells; insulin; deoxyadenosine; mitochondrial polarity; Drosophila; chitinase like proteins; cell culture; adenosine; imaginal disc cells; insulin; deoxyadenosine; mitochondrial polarity